Nutritional Analysis of Few Edible Microgreens in Variable Growth Medium using XRF Technique - Mohanty, Aischarya; Mahahlik, Gyanranjan; Parida, Sagarika (Asian Journal of Biological and Life Sciences, 2020)
The aim of this study is to quantify different elements present in three different Microgreen species using XRF technique. Seeds of three species namely Vigna radiata L., Brassica nigra L., Trigonella foenum graecum L. were taken to grow as microgreens. Three species were grown in different growth conditions like soil and water. The leaves were collected and analyzed by X-Ray Fluorescence (XRF) analysis to find out the presence of different elements. The result revealed that different varieties of microgreens constitute the rich source of mineral elements which is variable depending upon the species. The elemental composition at various stages of microgreens in different growth medium was estimated. Microgreens could be an excellent way to provide the families staying in cities with seasonal fresh organic leafy green vegetable. Microgreens of T. foenum graecum L. Provides maximum potassium and calcium and can be taken for nutritional deficiencies. The microgreen grown in soil contains molecules instead of elements and therefore, microgreens grown in water medium are better for providing nutritional supplement. These microgreens can be grown in home with little space and effort to meet the nutritional requirement from these organic grown little greens to meet the demand of every household staying in cities.
Keywords: Microgreens; Mineral elements; Nutritional deficiencies; Quantify; XRF technique